A Patient Decision Aid for Men With Localized Prostate Cancer: A Comparative Case Study of Natural Implementation Approaches. Issue 1 (January 2020) - Stacey, Dawn; Taljaard, Monica; Breau, Rodney H.; Baba, Nicole; Blackmore, Terry; Boland, Laura; Carley, Meg; Wu, Robert Chi; Smylie, Jennifer; Légaré, France
Abstract : Background: There are multiple options for men diagnosed with localized prostate cancer. Patient decision aids (PtDAs) help empower individuals and reduce unwarranted practice variation, but few are used in clinical practice. Objective: We compared 2 programs implementing PtDAs for men with localized prostate cancer. Methods: This was a comparative case study. Case 1 was a hospital prostate pathway and case 2 was a provincial prostate pathway with 2 locations (2a, 2b). Nurses provided the men with PtDAs and answered questions. Data sources were as follows: ( a ) 2 years administrative data for men with localized prostate cancer, ( b ) clinicians survey and interviews, and ( c ) patients/spouses interviews. Analysis was within and across cases. Results: The PtDA was used with 23% of men in case 1 (95% confidence interval, 19.8%–26.1%) and 98% of men in case 2a (95% confidence interval, 96.5%–99.8%). The pathway was not implemented in case 2b. Men given the PtDA had positive experiences. Many clinicians supported the use of PtDAs, some adapted their discussions with patients, and others did not support the use of PtDAs. To increase use in case 1, participants identified needing a Canadian PtDA available electronically and endorsed by all clinicians. In case 2b, the provincial prostate pathway needed to be implemented. Conclusions: There was variable uptake of the PtDAs between the cases. Men who received the PtDA had positive outcomes. Several strategies were identified to increase or sustain PtDA use. Implications for Practice: Nurses have a key role in supporting men making decisions about prostate cancer treatment by providing PtDAs, answering questions, and advocating for men's preferences.